Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1186/s12966-018-0763-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an eHealth intervention aiming to promote healthy food habits from infancy -the Norwegian randomized controlled trial Early Food for Future Health

Abstract: BackgroundStrategies to optimize early-life nutrition provide an important opportunity for primary prevention of childhood obesity. Interventions that can be efficiently scaled-up to the magnitude needed for sustainable childhood obesity prevention are needed. The objective of this study was to evaluate the effects of an eHealth intervention on parental feeding practices and infant eating behaviors.MethodsThe Norwegian study Early Food for Future Health is a randomized controlled trial. Parents were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
183
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(202 citation statements)
references
References 66 publications
10
183
2
4
Order By: Relevance
“…A few other studies have reported on parental use and satisfaction of eHealth interventions targeting young children. One is the Early Food for Future health study, in which Helle et al [ 11 ] found that a high proportion of parents used the intervention website and were well satisfied. A recent paper from the Growing Healthy Program in Australia reported both quantitative and interview data on how parents used and whether they were satisfied with an infant health app, concerning mode of delivery and how the quality of the app was perceived [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few other studies have reported on parental use and satisfaction of eHealth interventions targeting young children. One is the Early Food for Future health study, in which Helle et al [ 11 ] found that a high proportion of parents used the intervention website and were well satisfied. A recent paper from the Growing Healthy Program in Australia reported both quantitative and interview data on how parents used and whether they were satisfied with an infant health app, concerning mode of delivery and how the quality of the app was perceived [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The participants had the opportunity to not answer or complete the questionnaire without stating any reasons, hence we have no data regarding grounds for withdrawal. Outcomes at child age 12 months are previously reported [24], the outcome assessment at child age 24 months is reported here–se Supporting information S1 and S2 Files. The Norwegian Centre for Research Data evaluated and approved the study (http://pvo.nsd.no/prosjekt/43975), see Supporting Information S3–S5 Files.…”
Section: Methodsmentioning
confidence: 99%
“…The participants' use and experience with the intervention were reported in our previous paper [24]. For the current paper, the participants compliance to the intervention was assessed by asking participants if they had seen the intervention`s infant feeding videos and cooking films (all , most , about half , one or two , none) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations